Analisis Standar Pengelolaan Pendidikan Menengah Pertama Pada SMP Islam Terpadu Permata Gemilang Kota Tangerang Selatan - Arman Paramansyah; Jonisar Jonisar; Miftahul Hadi; Muhammad Yunus Rangkuti; Hanafiah Hanafiah; Sri Handayani (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The education system in Indonesia nationally has standards in its management. In general, education management standards are made to standardize the quality of management in schools/madrasas. However, it is specifically necessary to analyze each point in order to develop the quality of education services in schools/madrasas that implement it. This analysis must be able to support further progress for the development of educational institutions to become more professional and adapt to the needs of the community. Keywords: management standards, secondary education